Ambiguity and intrinsic structure in Matthew Arnold’s self-dependence: a literary analysis - Girsang, Martina; Sitorus, Elga Anggitha Br; Enjelyna, Enjelyna; Doloksaribu, Evita Lola; Tarigan, Joshua Pratama (Lembaga Riset Mutiara Akbar, 2026)
Literary works function as expressive mediums through which human thoughts, emotions, and philosophical reflections are articulated, and poetry represents one of the most condensed forms of such expression. This study examines Matthew Arnold’s poem Self-Dependence (1852) to investigate how intrinsic poetic elements construct meaning related to self-reliance and inner autonomy. Employing a descriptive qualitative approach, the research analyzes the poem stanza by stanza, focusing on structural and stylistic features including theme, imagery, tone, repetition, rhyme, and formal pattern. The findings reveal that linguistic devices operate systematically to mirror the speaker’s psychological transformation from existential uncertainty toward philosophical composure. In particular, repetition—most notably the phrase “forwards, forwards”—and symbolic natural imagery function as structural mechanisms that reinforce the poem’s central message of self-mastery independent of external validation. The study demonstrates that poetic meaning emerges through the interaction of formal elements rather than isolated devices. Ultimately, Self-Dependence remains intellectually relevant because it presents self-regulation as a response to modern psychological instability, illustrating how intrinsic analysis can uncover philosophical dimensions embedded within poetic form.